Learning from efforts to cost country plans: Priority technical issues to address - Connolly, Helen (International Food Policy Research Institute, 2014)
Background: In India, delivery of interventions to improve child nutrition requires active IC between the Ministries of Health and Family Welfare (MOHFW) and Women and Child Development (MWCD). This in turn requires linked actions in policy formulation, implementation, and monitoring & evaluation (M&E), but little is known about IC or how to optimize it.Objectives: To identify opportunities and challenges to achieving IC in policy, implementation and M&E for nutrition at the national level and in 2 states.Methods: Content analysis of policy & program documents, stakeholder interviews (n=38 national; 26 state).Results: Policy: Some shared objectives, an articulated need for IC, and diverse task forces support convergence in policy. Nutrition interventions are part of MOHFW programs, but nutrition is not a core objective. Implementation: Operational designs recognize need for coordinated frontline service delivery; delivery structures provide IC opportunities. However, personal relationships and shared understanding of work needs, rather than formal mechanisms facilitated IC. At state & district levels, facilitators were political commitment, will and leadership. M&E: Lack of common indicators and monitoring systems limit IC.Conclusions: There is potential to optimize IC but strong leadership, explicit roles and linked M&E systems could facilitate better IC for nutrition impact in India.Grant Funding Source: Supported by: Bill & Melinda Gates Foundation, through POSHAN , led by IFPRI